Patient, client, consumer, survivor or other alternatives? A scoping review of preferred terms for labelling individuals who access healthcare across settings. Issue 3 (7th March 2019) - Costa, Daniel S J; Mercieca-Bebber, Rebecca; Tesson, Stephanie; Seidler, Zac; Lopez, Anna-Lena
Abstract : Objectives: Use of the term 'patient' has been recently debated, compared with alternatives including 'consumer' and 'client'. This scoping study aimed to provide an integrated view of preferred labels across healthcare contexts and countries to clarify labelling preferences of individuals accessing healthcare. Design: Scoping study. Data sources: A preliminary literature search using GoogleScholar, Medline, Embase and PsycINFO found 43 key papers discussing terminology for labelling individuals accessing healthcare services. We then used citation chaining with PubMed and GoogleScholar to identify studies discussing term preferences among healthcare recipients. Eligibility criteria: No date limits were applied, and all healthcare settings were considered. Primary research studies examining terminology preferences of individuals accessing healthcare, published in peer-reviewed journals were eligible. Data extraction and synthesis: All authors extracted data regarding preferred term and study characteristics, and assessed reporting quality of the studies using criteria relevant to our design. Results: We identified 1565 articles, of which 47 met inclusion criteria. Six articles that examined preference for personal address (eg, first name) were excluded. Of the remaining 41 studies, 33 examined generic terms ('patient', 'client', 'consumer') and 8 focused on cancer survivorship. Of the 33 examining generic terms, 27 reported a preference for 'patient' and four for 'client'. Samples preferring 'client' were typically based in mental health settings and conducted in the USA. Of the eight cancer survivorship studies, five found a preference for 'survivor', and three 'someone who had had cancer'. Conclusions: Overall, healthcare recipients appear to prefer the term 'patient', with few preferring 'consumer'. Within general clinical and research contexts, it therefore seems appropriate to continue using the label 'patient' in the absence of knowledge about an individual's preferences. Reasons for preferences (eg, familiarity, social identity) and the implications of labelling for healthcare have not been investigated adequately, necessitating future empirical (including qualitative) research.